In-Bundle Surgeons More Likely Select Cemented Femoral Fixation in Total Hip Arthroplasty for At-Risk Patients: The Medicare Comprehensive Care for Joint Replacement Bundled Model. Issue 4 (October 2020) - Edelstein, Adam I.; Hume, Eric L.; Pezzin, Liliana E.; McGinley, Emily L.; Dillingham, Timothy R.
Abstract : Background: Bundled payment models for lower-extremity arthroplasty have been shown to lower costs but have not reliably improved quality. It is unknown how the bundled payment model may affect surgeons' decisions that impact the quality of arthroplasty care. The purpose of this study was to compare the utilization of femoral component fixation modes by surgeons performing total hip arthroplasties (THAs) in at-risk patients in areas subject to Medicare's Comprehensive Care for Joint Replacement (CJR) bundled payment model compared with patients treated by surgeons in areas exempt from the policy. Methods: Elective, primary THAs among elderly persons were identified from Medicare claims during 2017 and 2018, including the use of cemented or cementless femoral fixation. Multivariable regression models, applied to samples stratified by sex, were used to assess the association between CJR bundle participation and the use of femoral fixation mode. Analyses were adjusted for patient age, race or ethnicity, comorbidity burden, low-income status, and Census division of the hospital. Results: Of 118, 676 Medicare patients who underwent THA, 9.1% received cemented femoral components, and use of cement varied significantly by geographic region (p < 0.001). Patients who received cemented fixation, compared with patients who received cementless fixation, had significant differences in mean age (and standard deviation) at 78.3 ± 6.9 years compared with 74.5 ± 6.1 years (p < 0.001) for female patients and 77.3 ± 6.8 years and 74.2 ± 5.9 years (p < 0.001) for male patients; were more likely to be White at 94.0% compared with 92.7% (p < 0.001) for female patients and 95.1% compared with 93.8% (p = 0.046) for male patients; and had higher mean Elixhauser comorbidity index at 2.6 ± 2.2 compared with 2.3 ± 2.0 (p < 0.001) for female patients and 2.8 ± 2.4 compared with 2.4 ± 2.1 (p < 0.001) for male patients. In adjusted analyses, female patients in the CJR bundled payment model were more likely to have cemented fixation compared with female patients not in the CJR model (odds ratio [OR], 1.11 [95% confidence interval (CI), 1.05 to 1.16]; p < 0.001), whereas male patients in the CJR bundled payment model were less likely to have cemented fixation compared with male patients not in the CJR model (OR, 0.91 [95% CI, 0.83 to 0.99]; p = 0.029). Conclusions: In the bundled environment, surgeons were more likely to choose cemented femoral fixation for elderly female patients. This may be due to in-bundle surgeons being more risk-averse and avoiding cementless fixation in patients at risk for fracture or implant-related complications. Further research is needed to directly examine the impact of the bundle on surgeon decision-making.